2018
DOI: 10.3889/oamjms.2018.245
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Diet, Dietary and Oral Hygiene Habits with Caries Occurrence and Severity in Children with Autism at Dammam City, Saudi Arabia

Abstract: AIM:The purpose of the study is to achieve the baseline information of the autistic child’s oral health status about the diet, dietary and hygiene habits. The association of these factors with dental caries were assessed.MATERIAL AND METHODS:The survey was composed of self-administered questionnaires to parents about their children’s’ demographic data followed by questions related to diet, dietary and hygiene habits. This is later followed by oral examination for estimating the decayed, missing and filled [dmf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 34 publications
2
42
0
Order By: Relevance
“…The results for the oral hygiene status in children with autism are largely controversial, varying from very good to very poor. Several studies have reported good oral hygiene in participants with ASD [9,[26][27][28], but others have indicated poor oral hygiene [29][30][31][32], which was also supported by our results.…”
Section: Resultssupporting
confidence: 91%
“…The results for the oral hygiene status in children with autism are largely controversial, varying from very good to very poor. Several studies have reported good oral hygiene in participants with ASD [9,[26][27][28], but others have indicated poor oral hygiene [29][30][31][32], which was also supported by our results.…”
Section: Resultssupporting
confidence: 91%
“…in the major progression of dental caries [8]. In addition, risk factors such as host susceptibility [9], age [10], dietary habits [11], socioeconomic and oral hygiene status [12] have been associated with increased incidence of dental caries [3,13,14] in human population.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers reported that although there are no oral diseases specifically associated with ASD, such patients suffer from a lack of dental care and oral hygiene, which may result in caries and/or periodontal disease. 16,17 In studies examining the oral health of children with ASD, gum disease, dental caries, bruxism, self-inflicted injury, dry mouth, malocclusion, nonnourishing chewing, and tongue pressure were reported. 18,19 The aim of this study was to compare the overall oral health status, oral Streptococcus mutans, and lactobacilli loads in children with and without ASDs.…”
Section: Introductionmentioning
confidence: 99%